Educating educators with social media - Wankel, Charles (Cutting-edge technologies in higher education,, 2011)
Social media are increasingly popular platforms for collaboration and quick information sharing. This volume is a collection of reports on how these technologies are being used to educate educators with social media in creative and effective ways. Social networking technologies enable the integration of students and alumni in co-curricular activities in exciting and still evolving ways. The use of wikis, blogs, LinkedIn, Facebook, Twitter, text messaging, Flickr, Delicious, YouTube, Yahoo Pipes, Diigo, Second Life, Moodle, and other Web 2.0 technologies are shown in vivid examples and insightful critiques. The processes, design, delivery and evaluation of instruction using social media are examined in detail and include such topics as: the use of social media in developing countries for new approaches to teaching as support for individual and peer-based learning; new teaching orientations premised on social media such as focused distraction; enhancing in-class participation; how instructors are increasing the technical expertise that is needed by educators to develop their own 21st century curricula projects; and creating an ecosystem for life-long learning through social media.